George Cruikshank - Thackeray, William Makepeace, 1811-1863 (Salt Lake City, UT : Project Gutenberg, 2006)
"George Cruikshank" by William Makepeace Thackeray is a biographical essay published in the early 19th century, specifically in the late 1830s. This work delves into the life and artistic contributions of George Cruikshank, a notable caricaturist and illustrator of his time. Thackeray highlights Cruikshank's humor, social commentary, and his role in reflecting the whims and follies of society through his art. In this piece, Thackeray pays homage to Cruikshank$1 (Bs unique approach to illustration and the joy he brings to children and adults alike through his playful and often satirical portrayals. The author reflects on childhood memories associated with Cruikshank$1 (Bs works, emphasizing his ability to evoke laughter and joy. Thackeray notes the intrinsic honesty in Cruikshank$1 (Bs character and artistry, which stands against political pretension and societal norms. Through anecdotes and detailed examinations of specific artworks, Thackeray presents Cruikshank not only as an artist but as a cultural figure whose illustrations serve to critique and entertain, fostering a connection to the everyday experiences of his audience. (This is an automatically generated summary.)s
Release date is 2006-05-22
Produced by Donald Lainson; David Widger
Keywords: Caricatures and cartoons -- Great Britain; English wit and humor, Pictorial; Cruikshank, George, 1792-1878